Introduction to the Special Issue on Innovation in Transportation-Enabled Urban Services, Part 1 - AGATZ, Niels (Institutional Knowledge at Singapore Management University, 2023)
Rapid developments in city infrastructure and technol-ogies are creating numerous opportunities and inspiring innovative and emerging urban services. Among these innovations, complex systems of urban transportation and logistics have embraced advances and have been reshaped significantly. They enable innovative new urban services, which are now booming and changing everyday life for urban residents.This special issue of Service Science explores perspectives on innovation in transportation-enabled urban services. We hope that the special issue will enhance the understanding of the planning, operation, and management of such services. Contributions are expected to demonstrate rigorous model development, economic/ econometric analysis, and decision-making tools based on optimization and/or data-driven approaches. Research in this special issue addresses the novel challenges and oppor-tunities that arise in these transportation/logistics systems and relevant transportation-enabled urban services